Pengaruh permainan kecil terhadap peningkatan kebugaran jasmani - Ashidqy, Abdul Zalil; Iqbal, Rahmat; Siswanto, Siswanto (Universitas Hamzanwadi, 2023)
The purpose of this study was to determine the effect of small games on increasing physical fitness which is expected to attract students to take part in physical education and health lessons so that their physical fitness increases. The approach in this study is a quantitative approach using the experimental method. The population used was class XI TKR 2 SMK Iptek Sanggabuana Pangkalan, totaling 38 people. The sampling technique uses total random. The research instrument used the Indonesian Physical Freshness Test (TKJI). Data analysis technique using pretest posttest design. The results showed that the pretest mean was 14.13 and the posttest mean was 16.61. The results of the paired sample t test analysis with the data obtained a significance value (2-tailed) = 0.000 which is less than the significance level (α) = 0.05, then H0 is rejected and Hl is accepted. So it can be concluded that the conclusion of small games has an effect on increasing physical fitness in class XI SMK Iptek Sanggabuana.